Quality of red tilapia viscera oil (Oreochromis sp.) as a function of extraction methods (2022)
ABSTRACT: This study aimed to propose a simple and efficient heating-freezing method for oil recovery from red tilapia (Oreochromis sp.) viscera, suitable for industrial application and that does not affect its composition. Three methodologies for oil extraction were studied: a) direct heating (69 C and 29 min) of samples followed by separation of the oil by decantation, b) direct heating with subsequent freezing and c) solvent extraction assisted by ultrasound. For the oil obtained by each methodology, the following factors were determined: peroxide and iodine values, oxidative stability index, yield percentages and fatty acid profile and, to evaluate the changes thereof, a thermal analysis by differential scanning calorimetry was performed. An oil extracted by centrifugation from fresh viscera was used as control. Results showed yields of 92,126%, 60,99% and 55,36% for the oil obtained by heating and freezing, heating and decanting and solvent extraction, respectively, the other evaluated parameters were similar among each other. The content of PUFA was not affected by heating when compared to the control oil, although a decrease was observed in the solvent extracted oil. This behavior was corroborated with the thermal analysis, which showed that the higher PUFA content, the lower the melting temperatures of the oils and the energy required for phase change. A principal component analysis allowed determining that while there are no differences in the abundance of fatty acids C20:1, 14:0, 18:0, 16:1 and C16:0, there are differences for fatty acids C18:1 and C18:2 depending on the method of extraction used in the oil obtention. The results of this study show that the heating-freezing extraction method is a good alternative for acquiring value-added products and facilitates their implementation in rural areas. Furthermore, allows obtaining a product with high content of polyunsaturated fatty acids (at least a third of the total content).